Optimization of Treatment of Patients with Chronic Cardiac Insufficiency of the Ischemic Genesis and Hobnail Liver - A. G. Evdokimova; A. E. Radzevich; A. V. Tomova; V. V. Evdokimov; E. V. Kovalenko; L. V. Zhukolenko (Антибиотики и Химиотерапия)
Clinical efficacy of combined therapy including the use of rifaximin and L-ornithin-l-aspartate , as well as the dynamics of the biochemical indices, the manifestation levels of portal-systemic-encephalopathy and intestinal microbiocynosis were investigated in patients with chronic cardiac insufficiency of ischemic genesis and hobnail liver. The combined therapy resulted in improvement of the patients clinical state, lower levels of the portal-systemic encephalopathy manifectation by decreasing hyperammonium, normalization of the large intestine microflora, and blood serum biochemical parameters.